Effects of vitamin D3 supplementation on oxidative stress and antioxidant enzyme after strenuous endurance exercise in healthy young men: a double-blind, placebo-controlled trial - Cheng-Tse Yang; Pei-Wei Weng; Li-Hui Chien; Sunil Kumar; Ming-Ta Yang (Biology of Sport)
Vitamin D 3 exhibits strong antioxidant properties. However, its effect on oxidative stress after strenuous endurance exercise remains unclear. Therefore, we investigated the effects of vitamin D 3 supplementation on strenuous endurance exercise-induced oxidative stress. In this study, 26 male participants consumed vitamin D 3 (5,000 IUs of vitamin D 3 daily for 4 weeks) or placebo. After four weeks, all participants performed strenuous endurance exercise at 65% of V̇O 2max . Blood samples were collected before and after four weeks of supplementation to determine the participants’ serum 25(OH)D concentration. Additionally, venous blood samples were collected before, immediately after, two hours after, and 24 hours after the strenuous endurance exercise test to analyze markers of oxidative damage (thiobarbituric acid reactive substances, and protein carbonylation) and antioxidant enzyme activity (catalase, glutathione peroxidase, and superoxide dismutase). After four weeks of vitamin D 3 supplementation, the concentrations of protein carbonylation and superoxide dismutase at post-0-h, post-2-h, and post-24-h were significantly higher in the placebo group than in the vitamin D 3 group (all p < 0.05); the concentration of thiobarbituric acid reactive substances was significantly higher in the placebo group than in the vitamin D 3 group at post-24-h ( p < 0.05); and the concentration of catalase was significantly higher in the placebo group than in the vitamin D 3 group at post-0-h ( p < 0.05). Our results indicated that four weeks of 5,000-IU vitamin D 3 supplementation (oil form) effectively increased the participants’ serum 25(OH)D concentration and mitigated the accumulation of strenuous endurance-exercise-induced markers of oxidative stress (e.g., thiobarbituric acid reactive substances and protein carbonylation).